Molecular Mechanism of β-Arrestin-Biased Agonism at Seven-Transmembrane Receptors - Reiter, Eric (2011)
The concept of biased agonism has recently come to the fore with the realization that seven-transmembrane receptors (7TMRs, also known as G protein–coupled receptors, or GPCRs) activate complex signaling networks and can adopt multiple active conformations upon agonist binding. As a consequence, the “efficacy” of receptors, which was classically considered linear, is now recognized as pluridimensional. Biased agonists selectively stabilize only a subset of receptor conformations induced by the natural “unbiased” ligand, thus preferentially activating certain signaling mechanisms. Such agonists thus reveal the intriguing possibility that one can direct cellular signaling with unprecedented precision and specificity and support the notion that biased agonists may identify new classes of therapeutic agents that have fewer side effects. This review focuses on one particular class of biased ligands that has the ability to alter the balance between G protein–dependent and β-arrestin-dependent signal transduction.